Comparative In Vitro Activity of Ceftolozane/Tazobactam against Clinical Isolates of Pseudomonas aeruginosa and Enterobacterales from Five Latin American Countries - Juan Carlos García-Betancur; Elsa De La Cadena; María F. Mojica; Cristhian Hernández-Gómez; Adriana Correa; Marcela A. Radice; Paulo Castañeda-Méndez; Diego A. Jaime-Villalon; Ana C. Gales; José M. Munita; María Virginia Villegas (MDPI AG, 2022)
Background: Ceftolozane/tazobactam (C/T) is a combination of an antipseudomonal oxyiminoaminothiazolyl cephalosporin with potent in vitro activity against Pseudomonas aeruginosa and tazobactam, a known β-lactamase inhibitor. The aim of this study was to evaluate the activity of C/T against clinical isolates of P. aeruginosa and Enterobacterales collected from five Latin American countries between 2016 and 2017, before its clinical use in Latin America, and to compare it with the activity of other available broad-spectrum antimicrobial agents. Methods: a total of 2760 clinical isolates (508 P. aeruginosa and 2252 Enterobacterales) were consecutively collected from 20 hospitals and susceptibility to C/T and comparator agents was tested and interpreted following the current guidelines. Results: according to the CLSI breakpoints, 68.1% (346/508) of P. aeruginosa and 83.9% (1889/2252) of Enterobacterales isolates were susceptible to C/T. Overall, C/T demonstrated higher in vitro activity than currently available cephalosporins, piperacillin/tazobactam and carbapenems when tested against P. aeruginosa, and its performance in vitro was comparable to fosfomycin. When tested against Enterobacterales, it showed higher activity than cephalosporins and piperacillin/tazobactam, and similar activity to ertapenem. Conclusions: these results show that C/T is an active β-lactam agent against clinical isolates of P. aeruginosa and Enterobacterales.